How Types of Facebook Users Approach News Verification in the Mobile Media Age: Insights from the Dual-Information-Processing Model - Ping Yu, Rebecca (Mass communication & society, 2021)
Because social media have become a primary means by which fake news is received and disseminated, verifying the accuracy of such news has become an increasingly critical practice for individual users. Drawing on the dual-information-processing model, this study uses two-wave panel survey data collected in Taiwan to investigate users' verification processes. Results reveal three user-types based on motivation for Facebook use-omnivores, entertainment-oriented mixers, and leisure-convenience seekers-and show that omnivores who are high in all motivations are more likely to engage in elaborative processing and subsequent verification of news than leisure-convenience seekers who use Facebook mainly for leisure and convenience purposes. Further, the indirect effects are weaker for entertainment-oriented mixers with higher levels of mobile Facebook use, compared to leisure-convenience seekers.